Effects of Melissa officinalis L. Extract on the Skin Tissues of Hyperlipidemic Rats - OZSOY SACAN, OZLEM; YANARDAG, REFIYE (Asian Journal of Chemistry, 2010)
In this study, the effects of Melissa officinalis L. on hyperlipidemic rats were investigated biochemically. The animals were fed a lipogenic diet consisting of 2 % cholesterol, 20 % sunflower oil and 0.5 % cholic acid added to normal chow and were given 3 % ethanol for 42 d. The extract was given gavage technique to rats a dose of 2 g/kg everyday for 28 d, after 14 d, experimental animals done hyperlipidemia. In hyperlipidemic groups, a reduction of the skin glutathione level (GSH), skin superoxide dismutase (SOD) activity and serum catalase (CAT), paraoxonase (PON) activity and an increase in serum cholesterol, total lipid, triglycerides and uric acid, γ-glutamyl transferase activity (GGT) and skin cholesterol, total lipid, lipid peroxidation (LPO), nonenzymatic glycosylation (NEG) and skin CAT, lactate dehydrogenase (LDH), glutathione peroxidase (GPx) and myeloperoxidase (MPO) activity were observed. Treatment with Melissa officinalis L. extract reversed these effects. Present results show that Melissa officinalis L. extract has a protective effect against skin tissue damage as result of hyperlipidemia, in addition to hypolipidemic effect.